2006
DOI: 10.1038/sj.ki.5001705
|View full text |Cite
|
Sign up to set email alerts
|

Adding a dialysis dose to continuous hemofiltration increases survival in patients with acute renal failure

Abstract: Acute renal failure (ARF) in critically ill patients is associated with high mortality. Optimal method and dose of continuous renal replacement therapy could improve survival in these patients. We studied the hypothesis that an increase in dialysis dose obtained by continuous veno-venous hemodiafiltration (CVVHDF) is associated with a better survival than continuous veno-venous hemofiltration (CVVH) among critically ill patients with ARF. In a prospective randomized trial, these two methods were compared in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
221
6
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(239 citation statements)
references
References 25 publications
5
221
6
7
Order By: Relevance
“…A recent single-centre randomized controlled study found that the addition of 1-1.5 l.h )1 of dialysate flow to CVVH at 1-2.5 l.h )1 was associated with a significant increase in 28-day and 90-day survival. It was suggested that the increased removal of small molecules by haemodialysis improved control of azotaemia, and this conferred the survival advantage [18]. However, other opinion has suggested that the increased overall treatment dose provided by the addition of the dialysis element may have been responsible for the survival benefit [19].…”
Section: Methodsmentioning
confidence: 99%
“…A recent single-centre randomized controlled study found that the addition of 1-1.5 l.h )1 of dialysate flow to CVVH at 1-2.5 l.h )1 was associated with a significant increase in 28-day and 90-day survival. It was suggested that the increased removal of small molecules by haemodialysis improved control of azotaemia, and this conferred the survival advantage [18]. However, other opinion has suggested that the increased overall treatment dose provided by the addition of the dialysis element may have been responsible for the survival benefit [19].…”
Section: Methodsmentioning
confidence: 99%
“…The use of RRT in this clinical setting is designed to optimize acid-base balance, small solute clearance, and volume control. Providing more intensive RRT (via greater solute clearance as measured by urea kinetic modeling) was, therefore, hypothesized to be beneficial (4)(5)(6). However, when tested in subsequent larger randomized, controlled trials, higher-intensity RRT in AKI has failed to improve outcomes compared with standard intensity therapy (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Haemofiltration, which is nowadays one of the most widely used hemopurification method in the ICU, failed to significantly reduce plasma cytokine concentrations and ameliorate organ dysfunction in septic patients when low ultrafiltration doses (2 l/h of plasma water exchange) were used [4]. In contrast, the importance of dialysis intensity to improve the outcome of critically ill patients with acute renal failure has been demonstrated [5][6][7]. Nonetheless, although the minimal ultrafiltration rate of 35 ml/kg per hour has been recommended [1,3], recent large multicenter trial, in which 63% of patients were septic, challenged the issue of a dosage-outcome relationship in patients with acute kidney injury [8].…”
Section: Introductionmentioning
confidence: 98%